The Effect of Using Electric Circuit Props Based on Bruner’s Thinking Stage of Concept Understanding Mathematics on Conjunctions and Disjunctions - Ginting, Atania Christianti Br; Mayasari, Fitria; Sinaga, Venina (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to determine the effect of using electric circuit props based on Bruner’s thinking stage on understanding mathematical concepts in conjunction and disjunction material in class X semester II SMA Negeri 1 Tarutung. The research method used is a quasi-experimental quantitative method. The research design used a post-test only control group design. The instruments given to a sample of 32 in class X6 were taken randomly (random sampling). The research instrument used has been tested so that it is declared valid and reliable. By using the Liliefors test to test the normality of the students’ mathematical concept understanding score data, it was obtained that Lcount = 0.1289 when compared with Ltable for n = 30 and the significant level = 0.05, namely Ltable = 0.161, it turned out that Lcount < Ltable then the data from the students’ understanding of mathematical concepts is normally distributed. Because the two data are normally distributed, a hypothesis test is carried out. Based on the calculation of the regression analysis, the regression equation. In this equation, the linear regression direction coefficient (b) = 1.08 is positive, which means that the two variables have a positive linear relationship. Concept understanding will increase with the effect of using electric circuit props by 1.08 times. Based on the linear regression equation, the correlation coefficient is calculated, namely r = 0.8735. These results indicate that there is a strong relationship between the use of electric circuit props and understanding of mathematical concepts. Then from the calculation results, the coefficient of determination = 76.30% means that the influence between the use of electric circuit props on understanding mathematical concepts is 76.30%, and the rest is influenced by other variables or factors.